Nine-year outcome after anatomic stemless shoulder prosthesis: clinical and radiologic results - Hawi, Nael; Magosch, Petra (Journal of shoulder and elbow surgery, 2017)
Background: Several stemless shoulder implants are available on the market, but only a few studies have presented results with sufficient mid- to long-term follow-up. The present study evaluated clinical and radiologic outcomes 9 years after anatomic stemless shoulder replacement. Methods: This is a prospective cohort study evaluating the stemless shoulder prosthesis since 2005. Anatomic stemless shoulder replacement using a single prosthesis was performed in 49 shoulders; 17 underwent total shoulder replacement, and 32 underwent hemiarthroplasty. Forty-three patients were clinically and radiologically monitored after a mean of 9 years (range, 90-127 months; follow-up rate, 88%). The indications for shoulder replacement were primary osteoarthritis in 7 shoulders, post-traumatic in 24, instability in 7, cuff tear arthropathy in 2, postinfectious arthritis in 1, and revision arthroplasty in 2. Results: The Constant-Murley Score improved significantly from 52% to 79% (P < .0001). The active range of motion also increased significantly for flexion from 101° to 118° (P = .022), for abduction from 79° to 105° (P = .02), and for external rotation from 21° to 43° (P < .0001). Radiologic evaluation revealed incomplete radiolucency in 1 patient without clinical significance or further intervention. No revision caused by loosening or countersinking of the humeral implant was observed. Conclusions: The 9-year outcome after stemless shoulder replacement is comparable to that of third- and fourth-generation standard shoulder arthroplasty.